Impact Of Building Information Modeling on Design and Construction Firms in Arab Gulf Region (Public Building of Iraq as Case Study) - Radhwan Riyadh Abdulmaged AL-SABBAGH (Genius Journals, 2023)
The impact of building information modelling (BIM) on construction methods and architectural design in the Arab Gulf region is examined in this research. It is essential to deal with the difficulties brought on by this development given the rapidly increasing population in the area and the accompanying needs. The study focuses on Gulf BIM clients' utilization of BIM tools, primarily Autodesk Revit. According to the research, 70% of architects and building industry experts use Autodesk Revit. Additionally, 45% of businesses use information sharing to improve design cooperation and guarantee verifiable results through organized and reusable digital commerce. Additionally, 56% of businesses let staff members to change shared models, which improves collaborative workflows. Notably, 3D perspective views are extensively used in Arab Gulf public building plans to understand spatial arrangements and constraints. BIM implementation makes it easier to organize designs, lowering errors and disagreements while speeding up planning procedures in Gulf nations. Comparing actual and projected timelines is made possible by using visual scheduling tools for construction, which also makes earned value analysis and effective resource management possible. These developments in BIM technology help governments in the Gulf area handle architectural design processes with varied partners more effectively
Keywords: Bim; Building Construction; Arab Gulf